Effect of methotrexate on JAK/STAT pathway activation in myeloproliferative neoplasms. (26th February 2015) - Thomas, Sally; Fisher, Katherine; Snowden, John; Danson, Sarah; Brown, Stephen; Zeidler, Martin
Abstract: Background: The myeloproliferative neoplasms are a group of haematological malignancies characterised by pathological activation of the JAK/STAT (Janus kinase and signal transducer and activator of transcription) intracellular signalling pathway. 50–95% of patients have an acquired mutation ( JAK2V617F ) causing constitutive activation of JAK2. Our aim was to find new treatments for myeloproliferative neoplasms by identifying compounds that suppress JAK/STAT pathway activation. Methods: We used a luciferase-based transcriptional assay in the low complexity Drosophila model system to screen a library of 2000 small molecules for modulators of JAK/STAT pathway activation. Screen hits were validated with western blotting in the HDLM-2 Hodgkin's lymphoma cell line. The HEL cell line, in which constitutive JAK/STAT pathway activation is caused by JAK2V617F, was used to determine the relevance of screen hits for treatment of myeloproliferative neoplasms. Findings: Methotrexate and the chemically similar drug aminopterin were independently identified as strong inhibitors of the Drosophila JAK/STAT pathway, an effect conserved to human cells. Methotrexate did not affect protein phosphorylation in other intracellular signalling pathways. Methotrexate caused significant suppression of JAK/STAT activation in HEL cells at a concentration equivalent to that seen in patients taking low-dose oral methotrexate (p≤0·001). Interpretation: Our results suggest that methotrexate is a promising treatment for myeloproliferative neoplasms that could be translated into clinical trials after assessment in primary cells. These results are particularly relevant in myelofibrosis. Inhibitors of JAK1/2 improve symptoms and prolong life in myelofibrosis, but their use is limited by cost. Other existing therapies for myelofibrosis appear no more effective than placebo. Methotrexate might bring the benefits of JAK/STAT pathway inhibition at a lower cost. Funding: Cancer Research UK, Yorkshire Cancer Research, UK Medical Research Council, Wellcome Trust, EU Framework Cancer Pathways.